2006
DOI: 10.1002/pbc.21000
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric evaluation of platelet activation in chronic autoimmune thrombocytopenia

Abstract: Platelets from 42 patients (platelet counts median 42x10(9)/L, range 3-223x10(9)/L) with chronic idiopathic autoimmune thrombocytopenia (cAITP) were investigated for P-Selectin expression and PAC-1 binding. The results showed that the levels of P-Selectin positive platelets (n=20) were higher in cAITP than in controls (P<0.0001), and correlated with platelet counts (P=0.04). PAC-1 binding was increased in only six patients, and not correlated with platelet counts. There was no correlation of P-Selectin or PAC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…However, in respect of the status of platelets with regard to activation, the subject had been contentious for three reasons: Firstly, all reports do not suggest that platelets in ITP patients were activated [13,18]. Secondly, reports that suggested platelet activation, were not always talking about the same thing; some mentioned activation of GPIIb/IIIa integrin through binding of PAC-1 antibody (which purports to assay the activation status of GPIIb/IIIa, through a single immunodiagnostic method, without fully establishing conformational change by other methods), while others focused on markers such as P-selectin and GPIb and GP53 (CD63) [13,[18][19][20]. Furthermore, the assays performed to check the activation status tend to assay ''activability'' as well, and different studies used different activating reagents such as thrombin and ADP.…”
Section: Discussionmentioning
confidence: 99%
“…However, in respect of the status of platelets with regard to activation, the subject had been contentious for three reasons: Firstly, all reports do not suggest that platelets in ITP patients were activated [13,18]. Secondly, reports that suggested platelet activation, were not always talking about the same thing; some mentioned activation of GPIIb/IIIa integrin through binding of PAC-1 antibody (which purports to assay the activation status of GPIIb/IIIa, through a single immunodiagnostic method, without fully establishing conformational change by other methods), while others focused on markers such as P-selectin and GPIb and GP53 (CD63) [13,[18][19][20]. Furthermore, the assays performed to check the activation status tend to assay ''activability'' as well, and different studies used different activating reagents such as thrombin and ADP.…”
Section: Discussionmentioning
confidence: 99%
“…26 Protein A immunoadsorption therapy reduced platelet associated IgG and IgM in ITP patients and also reduced the percentage of circulating P-selectin-positive platelets, suggesting an immune mechanism for the increased circulating P-selectin-positive platelets. 27 Panzer et al reported an increased percentage of circulating P-selectin-positive platelets in adult chronic ITP patients 28 and that ITP patients with high platelet surface P-selectin in vivo showed reduced agonist-induced platelet activation. 29 Panzer et al subsequently reported 6 that P-selectin expression on circulating platelets of ITP patients did not correlate with bleeding score, whereas platelet count and von Willebrand factordependent platelet adhesion were inversely associated with bleeding score.…”
Section: Discussionmentioning
confidence: 99%
“…CD16 ϩ cells are expanded under infectious or inflammatory conditions, 9,10 although the exact mechanism for increase in CD16 ϩ monocytes is not known. The activation state of platelets in ITP was reported to be inversely correlated with platelet counts, 36 and it may be that, in patients with low platelet counts, platelet-derived factors either directly or indirectly through activation of other mediators play a role in increased peripheral numbers of CD16 ϩ monocytes. For example, the chemokine CX3CL1/fractalkine known for its ability to promote the survival of CD16 ϩ monocytes 37 was elevated, albeit not statistically significant, in blood and bone marrow of ITP patients.…”
Section: Discussionmentioning
confidence: 99%